2018
DOI: 10.1111/are.13766
|View full text |Cite
|
Sign up to set email alerts
|

Determining an effective density regime for rearing juvenileAustropotamobius pallipesin a small-scale closed system hatchery

Abstract: With recent advances in aquaculture techniques, captive-breeding of the endangered white-clawed crayfish Austropotamobius pallipes for restocking is becoming a widespread conservation method. Establishing optimal stocking densities for aquaculture is essential in maximizing productivity, and increases the likelihood of crayfish survival when released. A 240-day experiment took place using 2-month-old juvenile, captive-born, A. pallipes, within a small-scale, closed-circuit hatchery to investigate survival, gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…This was despite significantly lower numbers of crayfish within the cyst treatment groups during this time period due to mortalities. Previous studies have shown there is an increase in growth with a reduction in crayfish density (Nightingale et al, 2018), which was not observed in this case, and therefore suggests that diet was a limiting factor. Growth of the hatchlings (experiment B) was also significantly greater when fed live Artemia nauplii plus plankton diet (Live + P) than when they were fed the Live + NZ or Spanish diets.…”
Section: Hatchling Growthcontrasting
confidence: 81%
See 3 more Smart Citations
“…This was despite significantly lower numbers of crayfish within the cyst treatment groups during this time period due to mortalities. Previous studies have shown there is an increase in growth with a reduction in crayfish density (Nightingale et al, 2018), which was not observed in this case, and therefore suggests that diet was a limiting factor. Growth of the hatchlings (experiment B) was also significantly greater when fed live Artemia nauplii plus plankton diet (Live + P) than when they were fed the Live + NZ or Spanish diets.…”
Section: Hatchling Growthcontrasting
confidence: 81%
“…The reduction in A. pallipes growth experienced with several of the treatment diets from day 40-80 is typical for this species. In a recent paper by Nightingale et al (2018), a 240-day study of A. pallipes hatchlings, found growth was highest in the first 60-days (47.1% ± 6.6%). Growth then dropped to an average 14.1% ± 5.8% increase with every 60-day increment.…”
Section: Juvenile Growthmentioning
confidence: 95%
See 2 more Smart Citations